Ulnar-to-median nerve anastomosis in the forearm. Review and report of 2 new cases - Resende, Luiz Antonio de Lima [UNESP]; Adamo, A. S V [UNESP]; Kimaid, P. A T [UNESP]; Castro, H. A L [UNESP]; Canheu, A. C. [UNESP]; Schelp, Arthur Oscar [UNESP] (My University, 2000)
The ulnar-to-median nerve anastomosis in the forearm is a very rare occurrence, not mentioned in many anatomical text books. We found only 4 cases cited in medical literature. Here we describe 2 new cases, for which diagnosis was suspected when the compound muscle action potential of the abductor pollicis brevis muscle (APB), obtained by maximal stimulation of the median nerve at the elbow, was lower than that obtained at the wrist. The diagnosis was confirmed by stimulation of the ulnar nerve at the elbow, which evoked a compound muscle action potential of the APB with a clear negative initial deflection without volume-conducted potential.
Keywords: adult; aged; anatomical variation; case report; female; forearm; human; male; median nerve; neuroanatomy; ulnar nerve; Action Potentials; Adult; Aged; Elbow Joint; Evoked Potentials, Motor; Female; Forearm; Humans; Male; Median Nerve; Muscle, Skeletal; Ulnar Nerve; Wrist Joint